STRENGTHENING STRATEGIES FOR UNIVERSITY BUSINESS INCUBATORS: OPTIMIZING MARKET ACCESS AND PRODUCT REPEAT ORDERS FOR STUDENT ENTREPRENEURS - Hanny, Rissa; Suhud, Usep; Rizan, Mohamad (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This study aims to analyze strategic solutions for the development of student entrepreneurship by examining the roles of business incubators, market access, repeat order behavior, and consumer behavior. Using a survey method, data were collected from 150 student entrepreneurs from various universities who have participated in entrepreneurial activities and/or incubation programs. The findings show that access to markets remains a major obstacle, often caused by limited capital, scale of production, and distribution networks. Business incubators play a vital role in facilitating promotional support, training, and access to digital platforms, though not all incubators have provided adequate post-production assistance. Repeat order behavior is strongly influenced by product quality, pricing, emotional engagement, and branding strategies. Additionally, consumer behavior in student-run businesses is significantly shaped by perceived value, satisfaction, and local cultural relevance. Based on the analysis, the study proposes several strategic solutions, including strengthening university-based incubator ecosystems, enhancing digital marketing capabilities, leveraging brand storytelling, and building sustainable customer engagement models. These recommendations are expected to help student entrepreneurs improve their market reach, customer retention, and overall business sustainability.